Cognitive Impairment in Schizophrenia: Current Perspective - Aich, T.K.; Mahato, A.; Subedi, S. (Journal of Psychiatrists’ Association of Nepal, 2017)
Impairments in a variety of cognitive functions are found in patients with schizophrenia. These impairments affect a wide array of different cognitive abilities and are often of moderate to severe degree. Cognitive impairments appear to present across lifespan, detectable at the time of first episode of illness, probably predate the illness and manifest a generally stable course over time. Though cognitive impairment does not form a part of diagnostic criteria, it has been included in DSM-V and proposed to be included in ICD-11 as a schizophrenia course specifier. This review attempts to provide a broad overview of the domains, onset, severity and course of cognitive impairments in schizophrenia, with a focus on functional relevance and treatment possibilities. There is strong evidence for a relationship between cognitive impairment and vocational and functional impairment in individuals with schizophrenia.